Liver lesions produced by aflatoxins in Rana catesbeiana (bullfrog) - Grassi, Tony Fernando; Pires, Paulo Wagner; Barbisan, Luis Fernando; Dal Pal-Silva, Maell; Abou Said, Roueda; Viana de Camargo, Joao Lauro (Elsevier B.V., 2007)
This study describes alterations induced in Rana catesbeiana (bullfrog) liver after extended dietary exposure to aflatoxins (AFs). Bullfrogs of both sexes were fed for 120 days a commercial chow blended with a rice bran-based mixture of Al's containing 667.0, 11.65, 141.74, and 3.53 mg/kg of AFs B1, B2, G1, and G2, respectively. Animals were sacrificed on study days 45, 90, and 120. Severe and progressive liver lesions with structural collapse, increased hepatocyte and biliary duct cell proliferation, appearance of basophilic hepatocytes, and diffuse scarring, were observed at all time points. There were no quantitative alterations in the liver melanomacrophage centers of the AFs-exposed animals. Increased amounts of lipid hydroperoxides, indicative of ongoing oxidative stress, were more evident in the Addutor magnum muscle than in the AFs-damaged livers. No tumors were found in the R. catesbeiana livers after 120 days of exposure to relatively high doses of AFs. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Rana catesbeiana; bullfrogs; aflatoxins; liver toxicity